2020
DOI: 10.3390/w12092499
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the United Nations’ Watercourse Convention Indicators to Inform Equitable Transboundary River Sharing: Application to the Nile River Basin

Abstract: East African riparian countries have debated sharing Nile River water for centuries. To define a reasonable allocation of water to each country, the United Nations’ Watercourse Convention could be a key legal instrument. However, its applicability has been questioned given its overly generalized guidance and non-quantifiable factors. This study identified and evaluated appropriate indicators that best describe reasonable and equitable principles and factors detailed under Article 6 of the convention in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Most studies proposed drastic measures to decrease the frequency of flooding by adopting collaborative water resources management and to take steps towards the KRB treaty. On the other hand, Gari conducted a study about the application of equitable water resource utilization in the Nile River basin [19]. Gari's survey was about the applicability of the Principles of equitable water resource utilization as highlighted in Article 5 of the 1997 UN Convention on the Law of Non-navigational Uses of International Watercourses (UNWC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies proposed drastic measures to decrease the frequency of flooding by adopting collaborative water resources management and to take steps towards the KRB treaty. On the other hand, Gari conducted a study about the application of equitable water resource utilization in the Nile River basin [19]. Gari's survey was about the applicability of the Principles of equitable water resource utilization as highlighted in Article 5 of the 1997 UN Convention on the Law of Non-navigational Uses of International Watercourses (UNWC).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of international templates for countries with shared watersheds, such as the United Nations Watercourses Convention (UNWC) and the UN Sustainable Development Goal (SDG-2030). Article 6 of the UNWC outlines a series of actions to enable equitable water resource usage [19]. The UN SDG-2030 proposes a series of templates to identify the degree (Indicators 6.5.1) and proportion (Indicators 6.5.2) of the transboundary water resources management, including flood risk management.…”
Section: Discussionmentioning
confidence: 99%
“…This determines a phenomenon also known as "water grabbing", a situation in which a power actor takes control or diverts water resources to their advantage, taking them away from local communities or entire nations, whose livelihood is based on those same resources and those same ecosystems that are plundered. As a result, conflicts and competitions over water quantity often arise, which further exacerbate the availability of water resources in Countries already tested by water scarcity, resulting in intermittent water supply [85][86][87][88]. In this regard, De Stefano et al ( 2010) [89] have shown that the totality of existing conflicts directly concerning the control of water resources does not manifest itself in military actions, but political tensions and instability in relations between states.…”
Section: (Ii) Transboundary Waters Issuesmentioning
confidence: 99%
“…Water resources of the Euphrates River basin have been severely depleted by the numerous dams built in Turkey, which have reduced, by 1/3, the water flow to the two downstream Countries, (Syria, Iraq) which risk serious drought. Turkey can exploit its dominance in terms of economic strength, political influence, and military capability, while in the two Countries downstream, these aspects are limited due to their internal political fragmentation and weaker military status [86][87][88][89]92] Jordan Israel, Jordan, Syria…”
Section: Euphrates Turkey Syriamentioning
confidence: 99%
“…They demonstrate the pathways by which informal dialogue can develop a shared understanding amongst stakeholders and how this can influence basin planning and development. Gari et al [11] investigate a formal approach to water allocation in transboundary river basins based on the principles of the United Nations' Watercourse Convention. They develop a set of potential indicators for these principles and evaluate the application of selected indicators to water allocation amongst the countries of the Nile Basin.…”
mentioning
confidence: 99%